A general strategy for colloidal stable ultrasmall amorphous mineral clusters in organic solvents. Issue 2 (24th October 2016) - Sun, Shengtong; Gebauer, Denis; Cölfen, Helmut
Abstract : A general gas diffusion strategy using 10, 12-pentacosadiynoic acid as a ligand and ethanol as a solvent was developed to fabricate stable amorphous mineral clusters with a core size of less than 2 nm. Abstract : While nature exerts precise control over the size and chemical composition of minerals, this is still a challenging task for artificial syntheses. Despite its significance, until now, there are still no reports on colloidal mineral nanoparticles in the subnanometer range. Here we developed a general gas diffusion strategy using 10, 12-pentacosadiynoic acid as a ligand and ethanol as a solvent to fabricate stable amorphous mineral clusters with a core size of less than 2 nm. First discovered for CaCO3, the method was successfully extended to produce monolayer protected clusters of MgCO3, SrCO3, Eu2 (CO3 )3, Tb2 (CO3 )3, Ce2 (CO3 )3, Ca x (PO4 ) y, CaC2 O4 and their hybrid minerals, Ca x Mg y (CO3 ) z and Ca x (CO3 ) y (PO4 ) z . All the mineral clusters can be well dispersed in organic solvents like toluene, and are stable for a long period without further crystallization. Our work paves a way for the artificial synthesis of colloidal mineral clusters, which may have various uses in both fundamental research and industry.